Bio-inspired lamellar hydroxyapatite/magnesium composites prepared by directional freezing and pressureless infiltration. Issue 8 (15th April 2021) - Yang, Li-Kai; Jin, Quan; Guo, Rui-Fen; Shen, Ping
Abstract: Hydroxyapatite (HA)/magnesium (Mg) composites are a promising alternative material for bone repair in load-bearing sites. However, the poor wettability between Mg and HA as well as the extreme sensitivity of Mg to oxidation and high vapor pressure at elevated temperatures makes the preparation of HA/Mg composites rather difficult. Herein, a facile strategy for improving the wettability of HA by Mg was proposed to enable the successful preparation of bio-inspired HA/Mg composites via directional freezing and pressureless infiltration. SiO2 nanoparticles were introduced into the freeze-cast HA scaffold by doping or soaking to promote the spontaneous infiltration of the Mg melt. The resulting HA/Mg composites displayed a delicate biomimetic lamellar structure with alternating ceramic/metal arrangements and demonstrated higher compressive strength (increased by 140%) and wear resistance (increased by 1200%) than porcine bones. In addition, the composites exhibited progressive degradation and surface apatite mineralization in a simulated body fluid environment, making them potentially promising for biomedical applications. This study provides a facile and tailorable method for the design and preparation of novel Mg-matrix composites with bio-inspired structures and biomedical functions.